The Second-Year Students’ Ability in Using Simple Past Tense Through Narrative Text at Palopo Cokroaminoto University - Juwita Crestiani M; Muhammad Hasby; Ardhy Supraba; Hermini; Opik Dwi Indah; Reki Pilu (Universitas Islam Negeri Palopo, 2026)
This research deals with to find out and describe the ability of the second-year students in using Simple Past Tense through narrative text at Cokroaminoto Palopo University. The population of this research was all the second-year students of Elementary School Teacher Education Study Program in academic year 2025-2026. The total sample was 30 students. The researcher used the purposive sampling. Based on the findings and discussion, the researcher concludes that the second-year students of the Elementary School Teacher Education Study Program at Cokroaminoto Palopo University have a good ability in using the Simple Past Tense through narrative text. This conclusion is supported by the students’ mean score of 75.5, which falls into the good category according to the classification criteria. The findings revealed that most students were able to identify and apply the Simple Past Tense correctly in narrative texts. They demonstrated an understanding of past verb forms, sentence structures, and the use of regular and irregular verbs.